Comparison of injective related reactions following ofatumumab and ocrelizumab in patients with multiple sclerosis: data from the European spontaneous reporting system - Scavone, Cristina; Anatriello, Antonietta; Baccari, Isabella; Cantone, Andrea; Di Giulio Cesare, Daniele; Bernardi, Francesca Futura; Moreggia, Ornella; Liguori, Valerio; Andreone, Vincenzo; Maniscalco, Giorgia Teresa; Capuano, Annalisa (Frontiers in Neurology, 2024)
Introduction In 2021 ofatumumab, a recombinant human anti-CD20 monoclonal antibody (mAb) already authorized for the treatment of chronic lymphocytic leukemia, received the marketing approval for the treatment of relapsing forms of multiple sclerosis (MS). Differently from ocrelizumab, that is administered intravenously, ofatumumab if the first anti-CD20 mAb to be administered subcutaneously without a premedication. Methods and objectives In this study we aimed to describe and compare the main characteristics of Individual Case Safety Reports (ICSRs) describing the occurrence of Injective Related Reactions (IRRs) following the treatment with ocrelizumab and ofatumumab reported in the Eudravigilance (EV) database during years 2021–2023. Results A total of 860 ICSRs with either ofatumumab and ocrelizumab as suspected drug were retrieved from Eudravigilance, of which 51% associated with ofatumumab and 49% with ocrelizumab. The majority of patients who experienced IRRs following ocrelizumab belonged to the age group of 18–64 years (73%), while the age-group was mostly not specified (55%) in ICSRs reporting ofatumumab as suspected. The distribution of gender was almost similar in the two groups, with the majority of ICSRs related to female patients. “Pyrexia” was the Preferred Term (PT) most reported for ofatumumab, while “Infusion related reaction” were more frequently reported with ocrelizumab. Premedication drugs were reported in 148 ICSRs. Out of 89 ICSRs for which the Time to Event (TTE) was calculated, 74 reported IRRs that occurred the same day of the drug administration. Discussion Based on the results of this study, although a risk of ofatumumab-induced IRRs cannot be excluded, it should be considered as manageable considering that the drug seems to be mostly associated with the occurrence of fever. Thus, it is important to continue to closely monitor the use of these in clinical practice to improve the knowledge on their long-term safety.